Previous experience of family violence and intimate partner violence in pregnancy - Ludermir, Ana Bernarda (2017)
OBJECTIVE To estimate differential associations between the exposure to violence in the family of origin and victimization and perpetration of intimate partner violence in pregnancy. METHODS A nested case-control study was carried out within a cohort study with 1,120 pregnant women aged 18–49 years old, who were registered in the Family Health Strategy of the city of Recife, State of Pernambuco, Brazil, between 2005 and 2006. The cases were the 233 women who reported intimate partner violence in pregnancy and the controls were the 499 women who did not report it. Partner violence in pregnancy and previous experiences of violence committed by parents or other family members were assessed with a standardized questionnaire. Multivariate logistic regression analyses were modeled to identify differential associations between the exposure to violence in the family of origin and victimization and perpetration of intimate partner violence in pregnancy. RESULTS Having seen the mother suffer intimate partner violence was associated with physical violence in childhood (OR = 2.62; 95%CI 1.89–3.63) and in adolescence (OR = 1.47; 95%CI 1.01–2.13), sexual violence in childhood (OR = 3.28; 95%CI 1.68–6.38) and intimate partner violence during pregnancy (OR = 1.47; 95% CI 1.01 – 2.12). The intimate partner violence during pregnancy was frequent in women who reported more episodes of physical violence in childhood (OR = 2.08; 95%CI 1.43–3.02) and adolescence (OR = 1.63; 95%CI 1.07–2.47), who suffered sexual violence in childhood (OR = 3.92; 95%CI 1.86–8.27), and who perpetrated violence against the partner (OR = 8.67; 95%CI 4.57–16.45). CONCLUSIONS Experiences of violence committed by parents or other family members emerge as strong risk factors for intimate partner violence in pregnancy. Identifying and understanding protective and risk factors for the emergence of intimate partner violence in pregnancy and its maintenance may help policymakers and health service managers to develop intervention strategies.